1993
DOI: 10.1159/000168660
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Study of Azathioprine versus Cyclosporin in Live-Donor Kidney Transplantation

Abstract: A total of 112 recipients of haploidentical live-related donor kidney transplants were assigned randomly prior to transplantation to two groups of immunosuppressive treatment. The first group (54 patients) received the conventional immunotherapy of azathioprine (AZA) and prednisolone (P; AZA-P group). In the second group, 58 patients were given cyclosporin (Cs) and P (Cs-P group). All patients had previous third-party blood transfusions. The follow-up period ranged from 3 to 6 years (mean 50 ± 8 months) during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Our immunosuppressive protocols have previously been described in detail [3, 4, 5]from 1970s till the 1990s. All patients, before 1983, received azathioprine (2–3 mg/kg/day) and prednisolone (2 mg/kg/day, with subsequent tapering of the dose till 0.5 mg/kg/day after 1 month).…”
Section: Methodsmentioning
confidence: 99%
“…Our immunosuppressive protocols have previously been described in detail [3, 4, 5]from 1970s till the 1990s. All patients, before 1983, received azathioprine (2–3 mg/kg/day) and prednisolone (2 mg/kg/day, with subsequent tapering of the dose till 0.5 mg/kg/day after 1 month).…”
Section: Methodsmentioning
confidence: 99%
“…5 During the follow-up (50 ± 8 mo), patient and graft survival rates did not significantly differ between the 2 groups. Moreover, overall frequency of acute rejection episodes was not different, although the number of patients who experienced repeated rejections was higher in group 1, with mean serum creatinine levels markedly higher among the recipients in group 2.…”
Section: Prospective Randomized Trial Of Azathioprine Versus Cyclospomentioning
confidence: 84%
“…8 The long-term results after 20 years reported that triple therapy patients experienced higher incidence of both chronic rejection and liver diseases ( Table 2). 9…”
Section: Prospective Randomized Trial Of Azathioprine Versus Cyclospomentioning
confidence: 99%
“…In contrast, other reports showed improvement of long-term renal function after patients' conversion from a cyclosporine/steroid-based regimen to AZA/steroids or MMFlsteroids [17, 19, 22, 24, 321. Long-term results of randomized therapeutic protocols primarily devoid of CsA have been reported very rarely [8,181, because CsA rapidly became the cornerstone immunosuppressive drug for most centers in the past I Syears. Although CNI-free regimens, using some newly introduced drugs are currently under investigation [I I, 12, 231, the long-term tolerance and benefit of such strategies are not known.…”
Section: Discussionmentioning
confidence: 99%
“…Although many authors have analyzed the kidney graft outcome after CsA withdrawal [lo, 15,16,20,21,24,27,29,31,321, trials that do not include any CNIs are quite rare [8,181. Therefore, the real impact of CNIs on long-term graft outcome is difficult to assess.…”
Section: Introductionmentioning
confidence: 99%